Macroprudential policy and the inward transmission of monetary policy: The case of Chile, Mexico, and Russia. Issue 1 (28th September 2020) - Bush, Georgia; Gómez, Tomás; Jara, Alejandro; Moreno, David; Styrin, Konstantin; Ushakova, Yulia
Abstract: This paper studies whether domestic macroprudential policy may attenuate the inward transmission of monetary policy shocks from the United States to domestic bank lending growth in three emerging market economies—Chile, Mexico, and Russia. Identification relies on banks' heterogeneous exposure to prudential policies and the fact that foreign monetary policy shocks are exogenous from the perspective of these economies. After analyzing the effects of the aggregate domestic prudential policy stance, we focus on specific prudential policies targeting mortgage and consumer loans, as well as foreign‐currency deposits. Although our overall results are mixed, we find evidence that the strength of international monetary policy spillovers varies depending on the stance of domestic macroprudential policy. In particular, a tighter reserve requirement stance over foreign‐currency deposits in Chile dampens the effect of an international monetary policy shock on domestic local‐currency lending, but reinforces that on foreign‐currency lending, whereas in Russia, it dampens the effect on both local‐currency and foreign‐currency lending, although to different degrees. Prudential policies targeting the asset side of banks' balance sheets, such as mortgage loans or consumer credit, are found to amplify international monetary policy spillovers in some cases and attenuate it in others, depending on the country context.